Clinic and diagnosis and comorbidity of respiratory tuberculosis and viral pneumonia caused by Herpes simplex virus, Cytomegalovirus Human and SARS-CoV-2 in patients with late-stage HIV infection with immunodeficiency - Vladimir Yu. Mishin; Anastasiia V. Mishina; Dmitry A. Lezhnev; Aleksandr L. Sobkin; Ivan V. Shashenkov (ZAO "Consilium Medicum", 2022)
Aim. To study the features of the social status, clinic and diagnosis of respiratory tuberculosis comorbidity and viral pneumonia caused by Herpes simplex virus type 1, Cytomegalovirus Human and SARS-CoV-2 in patients with late-stage HIV infection with immunodeficiency. Materials and methods. The prospective study included 25 patients with respiratory tuberculosis comorbidity with Mycobacterium tuberculosis, herpesvirus and coronavirus pneumonia, and 21 patients with respiratory tuberculosis with cytomegalovirus and coronavirus pneumonia (1a and 2a main groups) and, respectively, 25 and 21 similar patients, but without coronavirus pneumonia (1b and 2b comparison group), in the late stages of HIV infection with immunodeficiency. For the etiological diagnosis of herpesvirus- and cytomegalovirus pneumonia, PCR was used to detect the DNA of Herpes simplex virus type 1 and Cytomegalovirus Human in the diagnostic material of the respiratory tract, and for the etiological diagnosis of coronavirus pneumonia, PCR was used to detect SARS-CoV-2 RNA. Statistical data processing was carried out using the Microsoft Office Excel 2019 program with the calculation of the average in the group and the standard error of the average, confidence interval. Results. The comorbidity of respiratory tuberculosis, herpes-, cytomegalo- and coronavirus pneumonia in patients with late-stage HIV infection, in the phase of progression and in the absence of ART was characterized by severe immunodeficiency and generalization of tuberculosis with multiple extrapulmonary lesions. This determines the similarity of clinical manifestations and visualization of CT changes in this comorbidity, which makes it difficult to distinguish them due to the simultaneous layering of several pathologies with the same type of clinical manifestations at once and requires a comprehensive etiological diagnosis of specific diseases to prescribe timely comprehensive treatment and reduce the lethality of this heavy contingent of patients. Conclusion. Patients with tuberculosis of the respiratory system and HIV infection registered in the office of tuberculosis care for HIV-infected in the tuberculosis dispensary represent a high risk group of infection with COVID-19 and CVP disease, and with severe immunodeficiency and GWP and CMVP, should be regularly subjected to preventive studies for timely detection of COVID-19 for the purpose of their emergency isolation and treatment.